Міжнародне співробітництво як один із пріоритетних напрямів підвищення ефективності підготовки працівників для органів та підрозділів Національної поліції України - Сокуренко, В. В.; Sokurenko, V. V.; Valerii Sokurenko (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 3(74). - С. 11–19, 2016)
Досліджено стан сучасної системи підготовки кадрів для Національної поліції України. Визначено, що міжнародне співробітництво в галузі підготовки поліцейських кадрів є новим перспективним напрямком міжнародної взаємодії у сфері протидії злочинності. Встановлено, що в сучасних умовах швидкого розвитку інтеграційних процесів у світі та значного зближення країн у різних сферах суспільного життя виникає потреба вчити поліцейських працювати в умовах інтенсивного розвитку міжнародного співробітництва.

The author has emphasized the fact that nowadays there is an urgent need for scientific analysis of the training system of police personnel in Ukraine; establishment of uniform standards of police personnel training, extension of cooperation within law enforcement area has become very important; the need to strengthen international cooperation in the sphere of police training has been enhanced. The author argues that international cooperation in the sphere of police personnel training is a new promising area of international cooperation in crime combating area. The direct participation of the National Police of Ukraine in this cooperation will develop an optimal model of police training. The state of international cooperation of Ukraine in the field of police personnel training at the universal, regional and bilateral levels has been considered in details. The author has offered to establish an international center for police personnel training on the basis of one of educational institutions, which train police officers. Herewith the author divides the standards that are to be trained for police officers into professional and those in the area of guaranteeing human rights.

Исследовано состояние современной системы подготовки кадров для Национальной полиции Украины. Определено, что международное сотрудничество в области подготовки полицейских кадров является новым перспективным направлением международного взаимодействия в сфере борьбы с преступностью. Установлено, что в современных условиях быстрого развития интеграционных процессов в мире и значительного сближения стран в различных сферах возникает потребность учить полицейских работать в условиях интенсивного развития международного сотрудничества.
International cooperation as one of the priorities in improving the efficiency of training officers for agencies and divisions of the National Police of Ukraine
Международное сотрудничество как одно из приоритетных направлений повышения эффективности подготовки работников для органов и подразделений Национальной полиции Украины
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Органи внутрішніх справ. Internal affairs agencies. Органы внутренних дел; поліція; підготовка кадрів; міжнародне співробітництво; міжнародний досвід; поліцейська освіта; стандарти підготовки поліцейських; модель підготовки поліцейських; протидія злочинності; police; полиция; подготовка кадров; международное сотрудничество; международный опыт; полицейское образование; стандарты подготовки полицейских; модель подготовки полицейских; противодействие преступности; combating crime; personnel training; international cooperation; police training; training standards; police training model